2007
DOI: 10.1111/j.1600-0633.2007.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Field observations and laboratory experiments on growth and lipid content of young-of-the-year perch

Abstract: Differences in growth and allocation of energy of youngof-the-year (YOY) perch (Perca fluviatilis) were studied in relation to both quantity and quality of food. Feeding on fish and Mysidacea, the mean size of YOY perch after the first growing season in Lake Pfeiffer was 152 mm. In contrast, YOY perch grew to 107 mm in Lake Speldrop and 83 mm in Lake Reeser Meer while mainly feeding on zooplankton. In correlation with food uptake and growth, the lipid content of YOY perch was significantly highest in Lake Pfei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 42 publications
0
19
1
Order By: Relevance
“…During night dives, we observed predation of H. anomala by bullheads (Cottus gobbio), larvae of dragonflies (Calopteryx virgo) and perch (Perca fluviatilis), confirming work of Kelleher et al in 1999, who found H. anomala in the stomach of perch in the delta of the Rhine in Holland. Others have come to the same conclusion (Borcherding et al 2007;Hermasch and Murawski 2007). The light of our projectors certainly disturbs the behavior of the animals and facilitates detection of H. anomala by predators, but it also makes it possible to highlight that many species eat this small shellfish.…”
Section: Discussionmentioning
confidence: 93%
“…During night dives, we observed predation of H. anomala by bullheads (Cottus gobbio), larvae of dragonflies (Calopteryx virgo) and perch (Perca fluviatilis), confirming work of Kelleher et al in 1999, who found H. anomala in the stomach of perch in the delta of the Rhine in Holland. Others have come to the same conclusion (Borcherding et al 2007;Hermasch and Murawski 2007). The light of our projectors certainly disturbs the behavior of the animals and facilitates detection of H. anomala by predators, but it also makes it possible to highlight that many species eat this small shellfish.…”
Section: Discussionmentioning
confidence: 93%
“…For this experiment, daphnids (D. galeata and D. hyalina) as well as L. benedeni were collected from Lake Speldrop, a small gravel pit lake near the Ecological Field Station in Rees-Grietherbusch (Borcherding et al 2007). In contrast to Lake Reeserward II, this lake is not connected to the River Rhine.…”
Section: Laboratory Predation Trialsmentioning
confidence: 99%
“…Organisms distributed across geographical gradients experience variation in stored energy requirements and patterns of higher storage in areas with harsher winters have been observed along latitudinal (Schultz and Conover 1997;Berg et al 2009;Jönsson et al 2009;Finstad et al 2010) and altitudinal gradients (Tracy 1999;Takahashi and Pauley 2010). Other factors that affect energy allocation include body size (Deegan 1986;Henderson et al 1988;Heulett et al 1995;Lampo and Medialdea 1996;Post and Parkinson 2001;Scott et al 2007), life history Jonsson 1998, 2003;Rikardsen and Elliott 2000;Morgan et al 2002), and food availability and quality (Heulett et al 1995;Garvey and Marschall 2003;Sogard and Spencer 2004;Borcherding et al 2007).…”
Section: Introductionmentioning
confidence: 96%